2000
DOI: 10.2307/3802989
|View full text |Cite
|
Sign up to set email alerts
|

Estimating Population Size of Grizzly Bears Using Hair Capture, DNA Profiling, and Mark-Recapture Analysis

Abstract: JSTOR is a not-for-profit service that helps scholars, researchers, and students discover, use, and build upon a wide range of content in a trusted digital archive. We use information technology and tools to increase productivity and facilitate new forms of scholarship. For more information about JSTOR, please contact support@jstor.org.. Allen Press is collaborating with JSTOR to digitize, preserve and extend access to The Journal of Wildlife Management.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

1
202
0
1

Year Published

2005
2005
2023
2023

Publication Types

Select...
8
1

Relationship

2
7

Authors

Journals

citations
Cited by 243 publications
(204 citation statements)
references
References 20 publications
1
202
0
1
Order By: Relevance
“…The resulting sample intensity was approximately 50% of the bears living in our study areas. We know this because population estimates were carried out in all six areas (Wielgus et al 1994;Mowat & Strobeck 2000;Boulanger 2001;M. Proctor, unpublished data;W.…”
Section: Resultsmentioning
confidence: 99%
“…The resulting sample intensity was approximately 50% of the bears living in our study areas. We know this because population estimates were carried out in all six areas (Wielgus et al 1994;Mowat & Strobeck 2000;Boulanger 2001;M. Proctor, unpublished data;W.…”
Section: Resultsmentioning
confidence: 99%
“…Movements among study areas across years are common however movements between individual simultaneous inventories are not common. During inventories in SW Alberta, the Elk and Flathead Valleys during 1997 only 2 male bears were detected on both sides of the continental divide (Mowat and Strobeck 2000). Similarly, in an inventory that spanned the South Rockies in Alberta and the Flathead Valley in BC during 2007, only 6 male bears were detected on both sides of the divide ).…”
Section: Mortalitymentioning
confidence: 97%
“…Gagneux et al [51] found an overall genotyping error rate of 37% among shed chimpanzee (Pan troglodytes verus) hairs but reduced error rate to < 0.01% using plucked hairs. Using one to four hair bulbs, genotype failure occurred among 37.3% of grizzly bear samples (Ursus arctos) [52] and 8% of black bear (Ursus americanus) and grizzly bear samples [53]. Goossens et al [45] examined the relationship between genetic identification failure and the number of roots in a sample and found failure rate declined as the number of roots in the sample increased.…”
Section: Discussionmentioning
confidence: 99%